2022
DOI: 10.1021/acsaelm.1c01193
|View full text |Cite
|
Sign up to set email alerts
|

Laser Direct Activation of Polyimide for Selective Electroless Plating of Flexible Conductive Patterns

Abstract: Flexible conductive patterns on polyimide substrates are attracting increasing research interest in the areas of wearables, biomedicals, automotives, and energy harvesters. This paper reports a laser-induced selective activation (LISA) process for electroless metallization and, therefore, the creation of complex conductive patterns on polyimide substrates. In this process, a Q-switched pulsed laser is utilized for scanning the surface and forming the catalytic layer consisting of microporous structures, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Figure 1d shows the comparison of the processing time between previously reported laser fabrications [26,[65][66][67][68] and this work for the synthesis of porous graphene with dimensions of 10 × 10, 100 × 100, and 200 × 200 mm 2 . The difference in production time was negligible in the small area of 10 × 10 mm 2 , while a significant decrease of more than 66.5 times was confirmed in large areas of 100 × 100 and 200 × 200 mm 2 .…”
Section: Fpg Fabrication Mechanism By Synergistic Photo-effectsmentioning
confidence: 88%
“…Figure 1d shows the comparison of the processing time between previously reported laser fabrications [26,[65][66][67][68] and this work for the synthesis of porous graphene with dimensions of 10 × 10, 100 × 100, and 200 × 200 mm 2 . The difference in production time was negligible in the small area of 10 × 10 mm 2 , while a significant decrease of more than 66.5 times was confirmed in large areas of 100 × 100 and 200 × 200 mm 2 .…”
Section: Fpg Fabrication Mechanism By Synergistic Photo-effectsmentioning
confidence: 88%
“…Reproduced with permission. [ 75 ] Copyright 2022, American Chemical Society. e) Representation of a writing system based on the use of a galvanometer system.…”
Section: Dlw Principles For Electronics Microfabricationmentioning
confidence: 99%
“…Third, Anderetta et al reported that the PAA solution showed feasibility for epoxy resin, but there was the most peeled metal observation along the grid lines among these studies [19]. Lastly, Ren et al have suggested the KNaC 4 H 4 O 6 solution for electroless plating on PI due to its verified excellent adhesive strength of 5B [20].…”
Section: Adhesion Strength Between Pekk-ni Coatingmentioning
confidence: 99%